Psychological features of application of non-normative vocabulary in interpersonal communication - Dysa, Olena; Chumak, Artem (Psychological Prospects Journal, 2022)
Purpose. The article considers the problem of using profane language in modern society, highlights the socio-psychological factors that contribute to the violation of the normative speech. It is noted that the uncontrolled flow of obscene language can be "activated" in an era of global historical turmoil and social instability. During the Russian-Ukrainian war, there was a linguistic and psychological imbalance between normative and non-normative vocabulary in the country (military conflicts, revolutions, threats of state collapse, economic crisis, etc.). The heterogeneity and multifunctionality of the researched issue are emphasized, those are both relevant and difficult to analyze at the present stage.The results of an empirical study of the peculiarities of the use of profanity by students of higher education institutions are presented.Methods. In this paper, methods of questionnaires and psychodiagnostics were used. The Mann-Whitney U-test was used to establish differences between groups and correlation analysis using the Spearman's rank correlation coefficient.Results. Psychological factors have been identified that determine the tendency to use obscene words in interpersonal communication. It is shown that a certain level of communicative abilities, aggression, reflection, social self-control, flexibility, speech anxiety and interpersonal emotional maturity differently affect the possibility of using profanity by students in the process of interpersonal communication. Relationships between verbal aggression and flexibility, independence, and interpersonal emotional maturity have been identified.Conclusions. The specifics of interpersonal communication is not a monolithic structure, it is multifunctional and dynamic. The results show that non-normative lexicon are served as a psychological instrument that is actively used in interpersonality communication, but by not everybody, and in most cases stipulated by a situation and individually-psychological features of personality. Non-normative speech constructs used in interpersonal communication may be perceived differently depending on the context and situation, and will not necessarily characterize the speaker as an uneducated and uncultured person. The results obtained by us significantly expand and supplement the existing research on the norms and culture of speech, which involves compliance with the norms of language, grammatical and stylistic rules, the appropriate use of speech constructions and more.
Keywords: normative speech, obscene language, culture of oral speech, non-normative speech constructs, interpersonal communication.